2013
DOI: 10.1099/vir.0.049221-0
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus LMP2A increases IL-10 production in mitogen-stimulated primary B-cells and B-cell lymphomas

Abstract: Epstein-Barr virus (EBV) latently infected B-cells are the precursors of EBV-associated malignancies. EBV-infection induces the production of pro-survival and anti-inflammatory cytokines that may be important in the transition between latency and malignancy. One EBV protein, LMP2A, can be detected in both latently infected resting B-cells and in EBV-associated malignancies. Therefore, we tested the ability of LMP2A to influence cytokine production using both LMP2A-Tg primary B-cells and LMP2A-expressing B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 43 publications
(49 reference statements)
2
40
1
Order By: Relevance
“…Our previous findings also indicate that LMP2A increases the levels of IL-10 RNA transcripts (Incrocci, McCormack, and Swanson-Mungerson, 2013) and therefore, we hypothesized that PI3K activation may result in the activation of a transcription factor that regulates IL-10 RNA levels. Since Signal Transducer and Activator of Transcription 3 (STAT3) increases IL-10 transcription (Gabrysova et al, 2014) and is regulated by PI3K (Hart et al, 2011), we hypothesized that the LMP2A-dependent activation of PI3K would result in STAT3 phosphorylation, which is a pre-requisite for STAT3 induction as a transcription factor (Harrison, 2012).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Our previous findings also indicate that LMP2A increases the levels of IL-10 RNA transcripts (Incrocci, McCormack, and Swanson-Mungerson, 2013) and therefore, we hypothesized that PI3K activation may result in the activation of a transcription factor that regulates IL-10 RNA levels. Since Signal Transducer and Activator of Transcription 3 (STAT3) increases IL-10 transcription (Gabrysova et al, 2014) and is regulated by PI3K (Hart et al, 2011), we hypothesized that the LMP2A-dependent activation of PI3K would result in STAT3 phosphorylation, which is a pre-requisite for STAT3 induction as a transcription factor (Harrison, 2012).…”
Section: Resultsmentioning
confidence: 86%
“…LMP2A is a BCR mimic that directly promotes B cell survival through a RAS/PI3K dependent pathway (Portis and Longnecker, 2004) and indirectly by inducing IL-10 production in both LMP2A-expressing primary murine transgenic B cells and in B cell lymphomas (Incrocci, McCormack, and Swanson-Mungerson, 2013). An additional study at the time indicated that the Syk inhibitor, R406, blocked the enhancement of IL-10 production in EBV-positive tumor cells from post-transplant lymphoproliferative disease (PTLD) patients (Hatton et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations